2020
DOI: 10.20473/jn.v14i3.17219
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Therapeutic Communications with Postoperative Patient Satisfaction in Islamic Hospital of Sultan Agung Semarang

Abstract: Introduction: Weaknesses in applying therapeutic communication are still a problem for nurses. This affects the quality of nursing services that have an impact on patient satisfaction. The purpose of this study was to identify the relationship between therapeutic communication and postoperative patient satisfaction.Methods: This research method was an analytical survey method used a cross sectional approach. Respondents in this study were postoperative patients who were treated in RSISA inpatient ward with 127… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
3
2
0
1
Order By: Relevance
“…This is because, according to (Dagun, 2002), women are more emotional than men, such as more easily offended, more easily influenced, and very sensitive. This is also in accordance with research conducted by (Wahdatin et al, 2019), which says women are psychologically more sensitive than men, making them more sensitive to receiving various signs in communicating with others. This is supported by the opinion of (Lotfi et al, 2019), which stated that there is a significant direct relationship between gender, communication quality, and patient satisfaction.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…This is because, according to (Dagun, 2002), women are more emotional than men, such as more easily offended, more easily influenced, and very sensitive. This is also in accordance with research conducted by (Wahdatin et al, 2019), which says women are psychologically more sensitive than men, making them more sensitive to receiving various signs in communicating with others. This is supported by the opinion of (Lotfi et al, 2019), which stated that there is a significant direct relationship between gender, communication quality, and patient satisfaction.…”
Section: Resultssupporting
confidence: 91%
“…The result of this study are in line with research conducted by (Wahdatin et al, 2019), which showed that there is a significant relationship between therapeutic communication with post-operative patients at RSI Sultan Agung Semarang, and it is also said that the better the nurse's therapeutic communication, the higher the patient satisfaction and the worse the nurse's therapeutic communication, the lower the patient satisfaction. This study's result also in line with study conducted by {Citation}, which stated that there was a significant relationship between nurses' therapeutic communication and patient satisfaction at Orchid Lounge Hospital BP Batam.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations